Secret Agent Jack Stalwart. [book 10], The Quest for Aztec Gold: Mexico - Singer Hunt, Elizabeth (Red Fox, 2006)
Destination: Mexico. The Global Protection Force has summoned Secret Agent Jack Stalwart to Mexico to hunt down a stolen map leading to hidden Aztec gold. Suddenly, he finds himself trapped in the hands of one of the most treacherous treasure hunters in the world. Can Jack stop Callous Carl and his band of thieves before they plunder again?